2013
DOI: 10.1002/ep.11763
|View full text |Cite
|
Sign up to set email alerts
|

Determination of kinetic parameters of biomass samples using thermogravimetric analysis

Abstract: In this work, thermogravimetric analysis is carried out on four different biomass samples such as bagasse, coir–pith, groundnut shell and casuarina leaves to study their thermal behaviour. Analysis is put through in an inert nitrogen atmosphere from ambient temperature to 800°C at a heating rate of 10°C/min. Three reaction zones corresponding to dehydration, hemicellulose–cellulose degradation and lignin degradation are observed for all four biomass samples. The kinetic parameters such as activation energy, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…Conversion (α) in the pyrolysis of karanja seed cake is calculated from TGA data using the equation given below: (7) where m i , m α , and m f are initial, instantaneous, and final mass of the samples, respectively.…”
Section: Model-fitting Approachmentioning
confidence: 99%
“…Conversion (α) in the pyrolysis of karanja seed cake is calculated from TGA data using the equation given below: (7) where m i , m α , and m f are initial, instantaneous, and final mass of the samples, respectively.…”
Section: Model-fitting Approachmentioning
confidence: 99%
“…Experimental and theoretical studies on oxy‐fuel combustion have principally focused on coal combustion . Thermogravimetric analysis (TGA), drop tube furnace, wire‐mesh reactor, and Hencken burner combustion system have been experimentally used . Previous results have demonstrated that coal ignition is delayed in O 2 /CO 2 rather than in O 2 /N 2 atmosphere because the molar heat capacity of CO 2 is higher than that of N 2 and because CO 2 suppresses radical formation.…”
Section: Introductionmentioning
confidence: 99%
“…Since each constituent of the biomass degrades at a different rate according to its chemical composition, it seems unquestionable that the same kinetic parameters can be calculated for the whole thermal degradation . Figure shows the behavior of lntrue[true(ln(1α)true)/T²true] versus 1/ T for heating rates of 5, 15, and 30 K/min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Later, two temperature intervals were adopted to obtain consecutive kinetic parameters for the stages of devolatilization and char formation . In recent works, three intervals, corresponding to the stages of drying, devolatilization, and char formation, were defined for the kinetic analysis .…”
Section: Introductionmentioning
confidence: 99%